Combined interventional sialendoscopy and intraductal steroid therapy for recurrent sialadenitis in Sjögren's syndrome: Results of a pilot monocentric trial. (26th June 2017) - Capaccio, P.; Canzi, P.; Torretta, S.; Rossi, V.; Benazzo, M.; Bossi, A.; Vitali, C.; Cavagna, L.; Pignataro, L.
Abstract: Objectives: To evaluate the effectiveness of interventional sialendoscopy alone or combined with outpatient intraductal steroid irrigations in patients with sialadenitis due to Sjögren's syndrome (SS). Design: A pilot therapeutic study. Setting: ENT Clinics, Universities of Milan and Pavia. Study Population: We included 22 patients with SS of whom 12 underwent interventional sialendoscopy followed by intraductal steroid irrigations (group A), and 10 interventional sialendoscopy alone (group B). Outcomes Measures: The following outcome measures were considered and recorded before and after the therapeutic intervention: (i) number of episodes of glandular swelling, (ii) cumulative prevalence of patients with glandular swelling assessed by the specific domain, the EULAR SS Disease Activity Index (ESSDAI), (iii) severity of pain by means of a 0‐10 pain visual analogue scale (VAS), (iv) severity of xerostomia and other disease symptoms assessed by the EULAR SS Patient Reported Index (ESSPRI) and the Xerostomia Inventory questionnaire. Results: The postoperative reduction in the mean number of episodes of glandular swelling was 87% (95% CI: 77‐93) and 75% (95% CI: 47%‐88%) in the groups A and B, respectively. The percentage of patients with glandular swelling decreased from 41.7% to 0.0% in the group A and from 30.0% to 0.0% in the group B, respectively. Most of the patients experienced a subjective clinical improvement documented by the statistically significant reductions in the postoperative mean pain VAS (group A P <.001; group B P =.004), Xerostomia Inventory ( P <.001 and P =.003) and ESSPRI scores ( P <.001 and P =.008). Interventional sialendoscopy followed by outpatient intraductal steroid irrigations was more effective than interventional sialendoscopy alone, when pain VAS, Xerostomia Inventory and ESSPRI scores before and after treatment were analysed together using the multivariate Hotelling T 2 test ( P =.0173). Conclusions: This pilot study confirms that interventional sialendoscopy with steroid duct irrigation significantly reduces the number of painful episodes of sialadenitis and improves the subjective sensation of oral dryness and other disease symptoms in patients with SS. The study results also suggest that the improvement is greater when interventional sialendoscopy is combined with a cycle of outpatient steroid ductal irrigations. Larger controlled randomised studies are certainly needed to confirm these preliminary data.